Normative Theories of the Media - Clifford G. Christians , Theodore L. Glasser, Denis McQuail, Kaarle Nordenstreng, Robert A. White (University of Illinois Press, 2009)
The question of the role of journalism in a democratic society is so central that even students and practitioners of communication are used to taking it for granted. Yet, today, both journalism and democracy are challenged by great changes, ranging from information technology to the global economy. All of this is an invitation to examine critically the media’s place and task in society—in particular in societies where democracy is understood not only as a political system but as a culture. At issue is not only what is the role of journalism in society but above all what this role should be. Such a perspective of the media’s mission in democracy leads us to a normative level—beyond factual landscapes toward values and objectives. This book is inspired by two interrelated aims: one practical and the other theoretical. The practical motivation grows out of the fact that the field of journalism and mass communication has an ongoing need for more theoretical treatments of media and society in general, and journalism and democracy in particular. The best known book in this category, Four Theories of the Press, by Fred Siebert, Theodore Peterson, and Wilbur Schramm (1956), is badly outdated and without obvious successors (see the reviews by Merrill [2002] and Nerone [2002]). What is needed is an approach that has much of the same didactic clarity, but with foundations in normative and political theory that can deal more adequately with basic questions, such as: What is and what should be the media’s role in a democratic society? How do we classify media systems and journalistic traditions? These questions are more and more burning in the contemporary world, where earlier Cold War divisions are replaced by new divides. The theoretical motivation for this book is to respond to the intellectual challenge posed by scholars who are concerned with professional ethics, with a more responsible performance of the media industries, and with a more adiequate education of journalists. The academic study of journalism and mass communication has become established over the past fifty years. But it still remains inadequate for describing and explaining the media’s role and task in society—in short, in providing us with normative theory. And this intellectual challenge is becoming more and more acute in a world where cultures are clashing and media are converging.